Production of biodiesel from waste cooking oil by immobilized in pva-alginate-sulfate beads [electronic resource] - Abdulkarim Ali Deba, 1982- author; Fakulti Biosains dan Kejuruteraan Perubatan (2013)
Thesis (Master of Science (Biotechnology)) - Universiti Teknologi Malaysia, 2013